Increasing Epistemic Value And Rate Through Flow Value Co-Creation Perspective Of Service-Dominant Logic Theory - Dimas Wibisono (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – Flow value co-creation is a psychological condition where a person feels pleasure in using a product or service. This concept starts with Service-Dominant Logic Theory (SDL) which indicates that SDL tends in the domain of marketing services. Aim –This study aims to identify the mediation of Flow value co-creation (FVC) with Epistemic (EPV) and Rate (RT) variables. Design / methodology / approach – This study describes the unaffected relationship between Epistemic values and Ratings mediated by the new concept of Flow value co-creation. The PLS-SEM equation engineering model uses the retrieval technique. This study involved a total of 286 Y generations of Shopee application users Y. Findings – The results showed that Flow value co-creation increased Rate. Shopee application users especially the Y generation feel shared comfort. Conclusion - The FVC relationship to RT has a logical impact in which the more comfortable, enjoyable, and safe using an application, the better the RT. The model can be assumed that Flow value co-creation can mediate the inconsistency of complex debates from previous studies regarding Epistemic Correlation (EPV) at Rate (RT). Research implication – For startup makers in the form of applications to survive. First, updates for consumer users affect user enjoyment. Second, the evaluation of applications for target markets such as MSMEs and consumers in their use will have an impact on the market. Third, Flow value co-creation affects the stakeholders in improving application performance. Limitations – The number of respondents is only in the Bantul area and is under 300 respondents, the development of variables such as the length of time the user is used, the frequency of applications used through advertisements.